PENGARUH PERMAINAN ENGKLEK PESAWAT TERHADAP KEMAMPUAN MOTORIK KASAR ANAK KELAS B DI NGANJUK: THE EFFECT OF THE PLANE ENGLISH GAME ON THE GROSS MOTOR ABILITIES OF GRADE B CHILDREN IN NGANJUK - Rohmah, Shinta Nur Azizah (Thufuli : Jurnal Ilmiah Pendidikan Islam Anak Usia Dini, 2021)
The purpose of this study was to determine the effect of the plane crank game on children’s gross motor skills using a quasi experimental method. The population in this study were class B teachers in Kindergarten Pertiwi, Pace District, Nganjuk. Collecting data using a questionnaire technique with google form media. Analysis of research data using validity test, reliability test and regression statistical analysis. This study shows that teachers gave Aircraft Engklek games 3-5 times. In the plane crank game variable, there is an average pre-test score of 16.7 and a post-test score of 35.5. While the gross motor skills variable pre-test mean score was 17.3 and the post-test mean score was 35.3. Thus, the increase in gross motor skills of children is influenced by the movement of jumping with one leg with a presentation value of 49%, jumping on two legs by 20% and jumping in the box without falling by 31%. Based on the results of data analysis using SPSS 20 with a significance level of 0.05, the value was 0.034 or less than 0.05. From these results it can be concluded that the Aircraft Engklek game affects the gross motor skills of B grade children in Nganjuk.